“Inteligencia emocional y actitudes ante la muerte en el personal de salud del Hospital Andino Alternativo de Chimborazo, período febrero - julio 2016” - Alulema Moncayo, Adriana Carolina (2017)
The research project was carried out at the Andean Alternative Hospital of Chimborazo, during the period February - July, 2016; the main objective was to analyze Emotional Intelligence in Attitudes to Death in the staff of this institution. Work was carried out with the Health Personnel of the Palliative Care, Hospitalization, Emergency and External Consultation areas, with a population of 50 people and a non-probabilistic sample of 45 people chosen by the researchers applying the inclusion and exclusion criteria. Researchers used the scientific method, the descriptive, transverse design, the type of research was field and the level of research was exploratory. The data collection techniques and instruments used were: Trait Meta - Mood Scale TMMS-24 to determine the level of emotional intelligence skills and the Attitude to Death Test CAM-1 to know the attitudes that has the health personnel toward the death of their patients, followed by clinical observation.The techniques for the analysis of the results were processed using basic statistics of the Excel program, which when reviewed were represented in tables and graphs, and afterwards the conclusions and recommendations were reached. Once the investigation was concluded, it was evidenced that the Health Personnel of the Andean Alternative Hospital of Chimborazo has an adequate emotional perception corresponding to 62.22%, emotional understanding to 60% and an excellent emotional regulation in the doctor - patient relationship, 51.11%. 73.3% expressed a negative attitude towards the death of their patients. Based on the results obtained in the research, a "Psychological intervention plan based on Emotional Intelligence for Attitudes towards Death" was designed and will be put into practice for Hospital Health Personnel.